2012
DOI: 10.1007/s10853-012-6585-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microstructure evolution and precise solid fraction evaluation of A356 aluminum alloy during partial re-melting by a color etching method

Abstract: Spheroidization of Al grains is required for the production of semi-solid slurry either by a partial solidification route or partial re-melting route. In this research, A356 aluminum alloy was deformed and partially re-melted to semi-solid state. A segregation sensitive reagent (Weck's reagent) was used to reveal the inner microstructure of Al grains for the better understanding of the microstructure evolution during partial re-melting. Optical microstructure observation showed that the previously compressed A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Once the temperature of specimen reaches 581°C, specimen was quickly water quenched. The solid fraction of A356 Al alloy at 581°C is about 0.5 according our previous investigation [14].…”
Section: Materials and Processsupporting
confidence: 51%
“…Once the temperature of specimen reaches 581°C, specimen was quickly water quenched. The solid fraction of A356 Al alloy at 581°C is about 0.5 according our previous investigation [14].…”
Section: Materials and Processsupporting
confidence: 51%
“…Chicken eggshell can be used in commercial products to produce new materials, and it has been highlighted in recent investigation because of its renovation prospective. [6][7][8][9][10] Even though there have been several attempts to use chicken eggshell components for a variety of applications, its chemical composition and accessibility make chicken eggshell a probable source of biofiller-reinforced composites giving additional or improved thermal and mechanical properties. The other advantages of using chicken eggshell are its availability in bulk quantity with lightweight and being economical and environmental friendly.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain spherical grains, inducing plastic strain by cold compression before recrystallization and partial melting was adopted. 9,14) The billets were compressed axially by 33% at a room temperature as shown in Fig. 1(a).…”
Section: Materials and Semi-solid Processingmentioning
confidence: 99%
“…In our previous research, we reported that Weck's reagent is applicable to solve this problem. 9) Weck's reagent was developed by Weck and Leistner in the 1980s. 10) This reagent is a kind of color etchant and can be used to investigate the solute segregation in aluminum alloys.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation